Susan P. Mattern: The Prince of Medicine: Galen in the Roman Empire - Wilkins, John (Petits Propos Culinaires, 2014)
Susan P. Mattern: The Prince of Medicine: Galen in the Roman Empire: Oxford University Press, 2012: 368 pp., hardback, £20.